Late Quaternary structure and development of the northern Ningaloo Reef, Australia - Collins, Lindsay; Zhu, Z.; Wyrwoll, K.; Eisenhauer, A. (2003)
Ningaloo Reef, situated on the central west coast, is Australia's largest fringing reef system extending southward from 22 deg S for over 200 km. Its narrow lagoon is backed by a coastal plain, which is largely composed of an emergent Last Interglacial reef on the flank of folded Tertiary limestones. The west-facing reef is exposed to strong oceanic swells across a narrow (8 km) continental shelf. Climatic aridity, cyclones, tsunamis, and the poleward flowing Leeuwin Current all influence the reef system. Seismic profiling and a coring and dating program along a transect through a reef pass indicate two periods of reef development in the northern part of the reef: Holocene and Last Interglacial. Seaward of the crest, the Holocene reef forms either a prominent 500 m-wide bulge with 10 m of relief and an abrupt seaward slope, or a series of discrete patch reefs. Holocene reef development is limited to depths of less than 30 m and reaches a maximum thickness of ca. 10-15 m below the reef crest. U/Th TIMS dates from distal parts of the Last Interglacial section between -18 and -36 m give ages toward the end of the high stand (120-115 ka). Last Interglacial reef growth was more extensive of the two, filling much of the available accommodation space, perhaps as a result of a stronger Leeuwin Current. This substrate subsequently provided an antecedent foundation for Holocene reef development.